2012
DOI: 10.1111/j.1574-6941.2012.01374.x
|View full text |Cite
|
Sign up to set email alerts
|

The fingerprint of chemosymbiosis: origin and preservation of isotopic biosignatures in the nonseep bivalve Loripes lacteus compared with Venerupis aurea

Abstract: Endosymbionts in marine bivalves leave characteristic biosignatures in their host organisms. Two nonseep bivalve species collected in Mediterranean lagoons, thiotrophic symbiotic Loripes lacteus and filter‐feeding nonsymbiotic Venerupis aurea, were studied in detail with respect to generation and presence of such signatures in living animals, and the preservation of these signals in subfossil (late Pleistocene) sedimentary shells. Three key enzymes from sulfur oxidation (APS‐reductase), CO2 fixation (Rubi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
46
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(53 citation statements)
references
References 78 publications
(105 reference statements)
5
46
2
Order By: Relevance
“…() is the measurement of the differences between the isotopic values of the shell organic matrix (conchioline) and the soft tissues; the latter have lower δ 13 C org (about −3‰) and higher δ 15 N org (variable, but on average +1‰), which is consistent with the results of a later study by Dreier et al . (). As based on mollusc data, soft tissues have different isotopic values from shell organic matrix, to aid our discussion, we consider a simplified model of Δ 13 C org and Δ 15 N org between shell organic material and soft tissues as that calculated for bivalves (Mae et al .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…() is the measurement of the differences between the isotopic values of the shell organic matrix (conchioline) and the soft tissues; the latter have lower δ 13 C org (about −3‰) and higher δ 15 N org (variable, but on average +1‰), which is consistent with the results of a later study by Dreier et al . (). As based on mollusc data, soft tissues have different isotopic values from shell organic matrix, to aid our discussion, we consider a simplified model of Δ 13 C org and Δ 15 N org between shell organic material and soft tissues as that calculated for bivalves (Mae et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Dreier et al . ; Tornabene et al . ) indicated that, under certain circumstances, it is possible to detect ancient symbioses using shell organic matrix carbon and nitrogen isotope signatures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, isotopic signatures of symbiosis (cf. Dreier et al, 2012) offer opportunities for identifying and studying the geological histories of ancient symbioses in animal colonies.…”
Section: Discussionmentioning
confidence: 99%